Impelementasi Manajemen Humas Dalam Mewujudkan Visi Misi Lembaga Di SMP Plus Al Mubarak - Umar Hasibulah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2013)
Management is a something that is very important for the success of an organization. In fact the core of the management is how to manage and take advantage of all available resources effectively and efficiently to achieve success as expected. SMP Plus Al Mubarak As an educational institution has succeeded in realizing the vision and mission very well. One proof is the students who enroll each year exceeds the amount that has been targeted. The younger generation is educated, or at least affected and receive raw paradigm (worldview) modernization of Europe that led to the westernization (Westernization) which deprive the roots of the scientific tradition and civilization of the East that have a correlation integral Islamic civilization. So in such conditions Said Nursi emerged with its own ideas as an alternative solution to restore civilization of the Turks with the concept of education. For that urgency and relevance of integrating the three major elements of education in modern times can not be negotiable, scientists today should deepen science and religion as well as the scholars must also develop the science of modern science and technology with a bandage Qur'anic morality. Education must prioritize and integrate three main values, namely: spirituality, intellect and morality as well. With so then education becomes a decisive aspect for the progress of human civilization.